Unusual xanthomas in a young patient with heterozygous familial hypercholesterolemia and type III hyperlipoproteinemia - Feussner, Giso; Dobmeyer, Jürgen; Nissen, Henrik; Hansen, Torben Stiig (American journal of medical genetics, 1996)
We report on a 20-year-old man with the combination of two independent familial lipoprotein disorders: heterozygous familial hypercholesterolemia (FH) and type III hyperlipoproteinemia (HLP). Familial hypercholesterolemia was diagnosed by elevated total and low density lipoprotein cholesterol levels and family history. By denaturing gradient gel electrophoresis, DNA sequencing and restriction fragment length polymorphism analysis, a G→A splice donor mutation in intron 3 of the proband's low density lipoprotein receptor gene was identified as the underlying molecular defect. This mutation was described previously as a receptor-negative founder mutation in Norway (FH-Elverum) and subsequently in 6 unrelated heterozygous English patients, creating a severe phenotype of familial hypercholesterolemia. Type III HLP was confirmed by homozygosity for apolipoprotein (apo) E2 and an elevated ratio of very low density lipoprotein cholesterol to serum triglycerides (0.40; normal ratio about 0.20). The patient has unusual flat xanthomas in the interdigital webs of the hands which are normally not found in either disease. These dermatological findings might therefore be indicative of the rare combination of both disorders of lipoprotein metabolism in one individual. © 1996 Wiley-Liss, Inc.